Information: People still count - Miller, Beth (Documentation et bibliothèques, 1986)
In discussing the theme of the Joint ASTED-CLA Conference, the President of the Canadian Library Association stresses the need for personalised services in an era when technology and progress occupy a large place. She invites the readers to think seriously about the future of libraries and the future of information professionals.